2004
DOI: 10.1124/dmd.32.6.632
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Modeling of Formulated and Crystalline 3,3′-Diindolylmethane Pharmacokinetics Following Oral Administration in Mice

Abstract: ABSTRACT:3,3-Diindolylmethane (DIM) is a naturally occurring indole, which is currently under investigation as a potential chemopreventive agent. The concentrations of DIM in plasma, liver, kidney, lung, heart, and brain tissues were determined following oral administration of two different formulations to mice (250 mg/kg). Mice were sacrificed periodically from 0 to 24 h after administration of either a crystalline or an absorption-enhanced formulation (BioResponse-DIM; Indolplex) of DIM, and plasma and tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 27 publications
2
101
0
Order By: Relevance
“…Compared with a pure crystalline formulation, BR-DIM is suggested to have 50% higher bioavailability. 26 The half-life of DIM ranges from 2.6 to 4.5 hours, and there is a significant increase in the maximum concentration of plasma DIM at supplementation levels between 100 and 200 mg/d. 78 The recommendation for a tolerable single dose of DIM from BR-DIM has been established as 300 mg (4.3 mg/kg/ d).…”
Section: Mechanisms Of Action and Surrogate Endpoints In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with a pure crystalline formulation, BR-DIM is suggested to have 50% higher bioavailability. 26 The half-life of DIM ranges from 2.6 to 4.5 hours, and there is a significant increase in the maximum concentration of plasma DIM at supplementation levels between 100 and 200 mg/d. 78 The recommendation for a tolerable single dose of DIM from BR-DIM has been established as 300 mg (4.3 mg/kg/ d).…”
Section: Mechanisms Of Action and Surrogate Endpoints In Humansmentioning
confidence: 99%
“…However, after 24 hours, DIM is no longer measurable in brain tissue. 26 Metabolites of DIM are found in both human serum and urine but demonstrate significant clearance within 24 hours. 27,28 …”
Section: Metabolism Of Diindolylmethane From Indole-3-carbinolmentioning
confidence: 99%
See 1 more Smart Citation
“…One percent DIM added in the AIN-76A-based diets were prepared by Research Diets Inc. (New Brunswick, NJ) and stored at −20°C. The dose was chosen based in part on studies reported previously (26,27). In the present study, around 30 mg of DIM would be estimated to be administered to each TRAMP mouse per day when consuming AIN-76 diet containing 1% DIM (1% DIM diet).…”
Section: Diet and Animal Study Designmentioning
confidence: 99%
“…Anderton et al (31) developed a PBPK model to characterize the pharmacokinetic properties of DIM, and the plasma pharmacokinetics and biodistribution of DIM following oral administration, in mice (31). Future studies are required to determine the serum DIM concentrations in mice fed various doses of DIM.…”
Section: Discussionmentioning
confidence: 99%